2021
DOI: 10.1007/s40497-021-00282-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of entrepreneurial orientation on firm growth among Iranian agricultural SMEs: the mediation role of entrepreneurial leadership and market orientation

Abstract: Entrepreneurship orientation is a fundamental topic both in entrepreneurship and in management that has a critical role in the development of the firm. The purpose of this paper is to study the relationship between entrepreneurial orientation (EO) and firm growth, specifically, how entrepreneurial leadership and market orientation mediate the relationship between EO and firm growth. The population of this study is agricultural small- and medium-sized enterprises (ASMEs) across Tehran Province. The survey instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have found positive relationships between entrepreneurial leadership and firm performance. According to Karimi et al (2023), the growth of firm performance is based on the predicted growth of leadership and organizational development in identifying business opportunities. Entrepreneurial leadership is considered a decision-making process that will play a crucial role in improving firm performance (El Manzani et al, 2022;Harris and Ogbonna, 2001;Karimi et al, 2023).…”
Section: Bank Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found positive relationships between entrepreneurial leadership and firm performance. According to Karimi et al (2023), the growth of firm performance is based on the predicted growth of leadership and organizational development in identifying business opportunities. Entrepreneurial leadership is considered a decision-making process that will play a crucial role in improving firm performance (El Manzani et al, 2022;Harris and Ogbonna, 2001;Karimi et al, 2023).…”
Section: Bank Performancementioning
confidence: 99%
“…According to Karimi et al (2023), the growth of firm performance is based on the predicted growth of leadership and organizational development in identifying business opportunities. Entrepreneurial leadership is considered a decision-making process that will play a crucial role in improving firm performance (El Manzani et al, 2022;Harris and Ogbonna, 2001;Karimi et al, 2023). This indicates that the qualities of entrepreneurial leaders play an essential role in improving bank performance.…”
Section: Bank Performancementioning
confidence: 99%